Africa might have dodged a bullet, but systemic warnings abound for poverty reduction efforts on the continent (World Bank blogs) - Abay, Kibrom A.; Kurdi, Sikandra (CGIAR System Organization, 2022)
World Bank published a blog post written by research fellow Kibrom Abay and Sikandra Kurdi, Kibrom Tafere (Sustainability and Infrastructure Team of the Development Research Group), and Nishant Yonzan (World Bank). The blog post stated that there were lessons and warnings to take from Africa’s response to the Coronavirus pandemic. The pandemic was one of the largest global shocks in recent history. Fortunately, it did not increase extreme poverty in Africa as it was feared it would. Early simulations projected an increase in the number of poor by anywhere between 30 – 120 million in 2020. The reason for the lower-than-expected poverty increase across the continent may be a combination of things. First, states that are fragile and in conflict are relatively more affected by negative shocks compared to those not in conflict. Second, the pandemic also uncovered important vulnerabilities in social safety nets in Africa. Third, the pandemic tested traditional methods of targeting and delivering social support programs in Africa that target chronic poverty—not vulnerability to shocks—and have traditionally focused on rural areas. Social protection programming in Africa needs to be “shock-responsive” and evolve dynamically in response to the needs and challenges arising from covariate shocks.